Insights into Paper Souvenir Purchase Intention of Tourists in Nepal - Shrestha, Sajeeb Kumar; Neupane, Dasarath; Karki, Tej Bahadur; Mahat, Dipak (Nepal Journal of Multidisciplinary Research, 2024)
Background: Tourism plays a vital role in Nepal’s economy, and handmade paper souvenirs represent a unique cultural product often purchased by tourists. This study explores the factors influencing the purchase intention of Nepali handmade paper souvenirs, focusing on three key constructs: appearance, referrals, and product features. Methods: A quantitative approach using descriptive and causal research design was adopted to test hypotheses derived from a comprehensive literature review. Measurement and structural models were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) in Smart PLS 2.0 Results: The findings reveal that appearance (β=0.241, t=3.752) and referrals (β=0.322, t=4.995) significantly and positively influence tourists' purchase intention. However, product features (β=0.093, t=1.474) do not have a significant impact. The composite reliability (CR > 0.7) and average variance extracted (AVE > 0.5) confirmed the measurement model's validity. Discriminant validity was supported through cross-loadings and Fornell-Larcker criteria. Conclusion: This study concludes that appearance and referrals play crucial roles in driving tourists’ purchase intention for Nepali handmade paper souvenirs. In contrast, product features appear to be less influential. Marketers and souvenir producers should emphasize product aesthetics and leverage word-of-mouth recommendations to boost sales. Novelty: This research uniquely integrates cultural aesthetics and social influence to understand the dynamics of souvenir purchasing in Nepal. By identifying key factors influencing buying decisions, the study provides actionable insights for enhancing marketing strategies for handmade cultural products.